Constituting Life Cycles: Circularity as Architectural Design Premise - Moodley, Keyur (School of Architecture, Planning and Geomatics, 2024)
The research elucidates the glaring certainty that the world we inhabit is a finite resource and environmental sustainability needs consideration and pre-thought. There is a clear need for sensitive applications in the future of the architecture, engineering and construction industries. The discourse makes comparisons between normative practices of development and natural quiddity. This comparison surfaces the differing processes of anthropic development and natural systems. Emerging from this is a clear need for future spatial practice to emulate systematic processes seen in our natural environments - a repositioning of architecture from linear metabolisms to circular ones. This is a method of creating architecture that speaks to the ability to adapt to change and achieve strategic circularity. The research discusses the design requirements needed in order to achieve this level of change and impermanence. These principles consider the constituting elements of a building and its lifespan, furthermore, post lifespan adaptation is also regarded with high importance. The design requirements are also considered as flexible and moderately compromisable when encountering the realities of a site. This evolves into a propositional design which aims to establish the exemplification of the established theories. The Artscape Precinct has been chosen for two main reasons. The first being the city's desires to create multifunctional and sustainable spaces in Cape Town's CBD and the second being the test to extend the lifespan of current buildings at a place currently known for its exhibitive qualities. A program of preparation and exhibition are realised through of a place of entertainment and instruction in proximity extending the primary function of the Artscape Theatre. The new aims to serve the program of the existing while clearly showcasing newer ways of composing layers of a building – from the macro scales of a site down to the micro scales of materiality that combines to create spaces. This is justified when aiming for sensitive contextual responsiveness and aiming to create a building that is emergent from its site. Conclusively, the established design requirements reorientate architecture towards sustainable practices of longevity through change.